Tradução e validação da Escala Nordoff Robbins de Comunicabilidade Musical - Aline Moreira Andre (2017)
The Nordoff Robbins Scales have been used since the 1960s in the USA. For them to be used in Brazil, a validation process is required. This study aims to translate and validate for the Brazilian context the second Nordoff Robbins Scale, denominated Musical Communicativeness Scale. The validation methodology follows the Model developed by Herdman, Fox-Rushby and Badia (1988), divided into six stages: conceptual equivalence, item equivalence, semantic equivalence, operational equivalence, measurement equivalence and functional equivalence. These stages were verified from 3 independent studies. In study 1, we verified the conceptual equivalence trough a literature review was done on the use of the Nordoff Robbins Scales in their original context. Studies related their use by working with autistic population, neurodevelopmental disorders, general music education of children and adolescents, and theoretical music studies. We also note the use of the Nordoff Robbins Scales in conjunction with other tests. In study 2, we verified the following were equivalences: of items, semantic and operational. In this study. This process of the Musical Communicativeness Scale translation occurred in 3 stages. The first step was to translate the manual and the Musical Communicativeness Scale from English to Portuguese. Two translators participated in this part of the study, one for doing the translation and another the revision of the text. In the second part a retranslation was made in Portuguese into English by one translator. In the third step, another translator was invited to analyze and compare the original text in English, the Portuguese version and the retranslation to English, in order to evaluate whether the text presented the same information and whether or not it required changes in writing. A questionnaire was applied in the third stage for the translator to justify his opinion. After the translation process, 10 evaluators were invited to fill out a questionnaire to verify the items of the Musical Communicativeness Scale, to verify the semantics of the explanatory manual and scale and to choose the best format. According to the evaluators the scale presents understandable language, its items are pertinent to the Brazilian context and may contribute to future research in music therapy in music. In study 3, we verified the equivalence of measurement, For this, we made an adaptation of the explanatory handbook of the Musical Communicativeness Scale was carried out and 4 examiners were invited to read this new adapted manual and to analyze 24 videos in music therapy on neurodevelopmental disorders. each lasting 30 seconds. After analyzing those 24 videos, the data were stored in the spreadsheet of Microsoft Excel 2016 and the Spearman correlation test was performed in SPSS 20.0 to verify interexaminers reliability of the Musical Communicability Scale. The result of interexaminers scores presented moderate and strong correlations (Spearman), indicating evidences of reliability for the translated Musical Communicativeness Scale and adapted to the Brazilian context. By means of the correlation of the interexaminers analyzes of the Scale, we found a moderate correlation in the body movement domain (=0,68) and strong correlations in the instrumental ( =0,79) and vocal domains (=0,87). We also found a strong correlation in Total Musical Communicativeness (=0,73). After verifying the positive results in the equivalences: conceptual, of item, semantic, operational and measurement, we believe that the Nordoff Robbins Musical Communicativeness Scale is functional for Brazilian context.